PENGARUH KARAKTERISTIK AUDITOR TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Manufaktur dan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Indira Saskara Giyatiyasa; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2026)
Taxes plays an important role in supporting the national economy. However, for companies, taxes are often perceived as a burden that reduces profits, thereby encouraging tax planning and tax avoidance practices. In the context of corporate governance, external auditors play a role in examining financial statements that may be related to tax avoidance practices. This study aims to examine the effect of auditor characteristics on tax avoidance in manufacturing and energy companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The auditor characteristics analyzed include audit industry specialization, audit fees, audit tenure, and audit opinion. Using purposive sampling, the final sample consists of 372 observations. Tax avoidance is proxied by the Effective Tax Rate (ETR), and multiple linear regression is employed as the analytical method. The results indicate that audit opinion has a positive and significant effect on tax avoidance, while audit industry specialization, audit fees, and audit tenure have no significant effect.